Needs of Guardians in Early Childhood Educational Management in Schools under the Loei Primary Educational Service Area Office1 - ศรีกระทุม, นิมลต์ ศรีกระทุม; ศรจันทร์, ชิษณพงศ์; พรมใจ, สมพงษ์ (Journal of Roi Et Rajabhat University, 2016)
early childhood educational management under the Loei Primary Educational Service Area Office1, Tha Li Educational Quality Group classified by level of education, monthly income and occupation. 159 guardians were selected as the sample of this study. The research instrument was a five-rating scale questionnaire. The data were analyzed using frequencies, percentages, means, and standard deviations. The research hypotheses were tested by t-test and F-test. The findings showed that the level of guardians’ needs was at a high level in all aspects. The aspects rated from the highest to the lowest were service, food and health, instructional activities and environmental management respectively. The result of the comparison of guardians’ needs in early childhood educational management of schools under the Loei Primary Educational Service Area Office1 indicated that there was significant difference at the level of .01 in the aspects of instructional activities, environmental management, food and health, safety, teachers and service. When compared the needs of the respondents’ classified by their level of education, income and occupation, there was significant difference at the level of .05.